The vulnerability of permafrost carbon to decomposition after thaw: exploring chemical and microbial controls - Ernakovich, Jessica G., author; Wallenstein, Matthew, advisor; Reardon, Ken, advisor; Conant, Rich, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: diversity; carbon-climate feedback; microbial ecology; permafrost; soil organic matter chemistry; methane